Development and Evaluation of Small Shaped Charge Jet Threats - Arthur DANIELS; Stan DEFISHER; Greg STUNZENAS; Nausheen AL-SHEHAB; Ernest L. BAKER (Problemy Mechatroniki, 2017)
Because of their prolific nature on the battlefield, rocket propelled and gun-launched grenades are of particular concern to the soldier, particularly because of the severe reaction that occurs when a munition is hit by the shaped charge jet. As a result of the danger that such a detonation poses, it is necessary to more precisely understand the behaviour of munitions subjected to these types of devices. In response to these threats, standardized 81 mm and 40 mm shaped charge warheads were developed for use during threat assessment testing to act as a consistent, lower-cost representative of shaped charge projectiles commonly encountered on the battlefield, and to help quantify the interaction of these jest with explosive charges. The international standards for shaped charge jet threat testing uses the Held initiation criteria V2D, where V is the jet velocity and D is the diameter. V2D was computationally predicted using the high-rate continuum models CALE and ALE-3D. The surrogate warheads were test fired through aluminium target plates to strip off jet mass to adjust the V2D to the threat munition.